2018
DOI: 10.3847/1538-4357/aad2df
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Systematic Survey of X-Ray Emission from Hydrogen-poor Superluminous SNe

Abstract: We present the results from a sensitive X-ray survey of 26 nearby hydrogen-poor superluminous supernovae (SLSNe-I) with Swift, Chandra, and XMM. This data set constrains the SLSN evolution from a few days until ∼2000 days after explosion, reaching a luminosity limit L x ∼10 40 erg s −1 and revealing the presence of significant X-ray emission possibly associated with PTF 12dam. No SLSN-I is detected above L 10 erg s-, suggesting that the luminous X-ray emission L x ∼10 45 erg s −1 associated with SCP 60F6 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 111 publications
(257 reference statements)
5
62
0
2
Order By: Relevance
“…We converted unabsorbed flux into the luminosity using luminosity-distance information. We found that the unabsorbed flux and X-ray luminosity of each Obs Id are typically similar to those estimated by Levan et al (2013) and Margutti et al (2018).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…We converted unabsorbed flux into the luminosity using luminosity-distance information. We found that the unabsorbed flux and X-ray luminosity of each Obs Id are typically similar to those estimated by Levan et al (2013) and Margutti et al (2018).…”
supporting
confidence: 81%
“…Along with the best-fit bolometric light-curve, the limiting X-ray luminosity ( 0.8 × 10 42 erg s −1 ) calculated using the stacked images obtained from Swift-XRT is also plotted (upper-left panel of Figure 2, black arrow); data reduction is discussed in Appendix .1.3. SN 2010kd is not visible in X-rays even near peak optical brightness, as seen in other XRT-observed SLSNe I except for PTF12dam (which was detected; Margutti et al 2018).…”
Section: Bolometric Light-curve and Model Fitting Usingsupporting
confidence: 61%
“…Our limits also point to very low density environments, consistent with previous findings that BL-Ic SNe favor low-density media (e.g., see Fig. 5 from Margutti et al 2018), as was also the case for SN 2002ap (Berger et al 2002) and SN 2010ay (Sanders et al 2012).…”
Section: Constraints On Uncollimated Outflows In Sn 2014adsupporting
confidence: 92%
“…Only two SLSNe I, out of roughly 30, show an X-ray signature: the Fast SCP06F6 (Lx ~ 10 45 erg s -1 ) [80] and the Slow PTF12dam (Lx ~ 10 40 erg s -1 ) [81]. The fact that the majority of the X-ray limits lie at 10 40 < Lx (erg s -1 ) < 10 45 [52,80,81] suggests that the X-ray emission associated with SCP06F6 is not common among SLSNe I [81]. The SLSNe I X-ray limits would point toward a magnetar magnetic field and ejecta masses similar to what is derived from light-curve models (3 M ≲ M ≲ 30 M) [ 22, 29, 43, 53, 55, 61, 83], and would disfavour CSM interaction as the main source of energy powering the light-curve [52,81].…”
Section: -X-ray Radio and Polarisation Signatures Of Superluminous Smentioning
confidence: 99%